Evaluación del centro de mercadeo agropecuario: servicio nacional de aprendizaje, centro de biotecnología agropecuaria, Mosquera (2019)
The objective of this article is to show evidence of the agricultural marketing center project at the Agricultural Biotechnology Center - C.B.A. of the National Learning Service - SENA in Mosquera, through the analysis of the application of an expert survey. A quantitative study of analytical, descriptive, non-experimental, transactional and field type was defined. A Delphi-type questionnaire was designed and applied to a sample of 22 agribusiness experts who were chosen from among technicians and professionals, SENA instructors, and small and medium entrepreneurs in the municipality of Mosquera. The questionnaire contained 6 items, 2 for the marketing variable and 4 for the project evaluation variable. Thus, it became evident that the development of a production accentuated in innovation and development in a collaborative way with the agricultural communities, can potentiate inter-institutional chains for the commercialization of agricultural products from SENA.